Palladium‐Catalyzed Benzofulvenation of o‐Arylanilines through C−H Bond Activation by Using Two Diarylacetylenes as an Implicit Benzofulvene. Issue 4 (20th December 2018) - Raju, Selvam; Hsiao, Huan‐Chang; Thirupathi, Selvakumar; Chen, Pei‐Ling; Chuang, Shih‐Ching
Abstract: We report the first example of Pd(II)‐catalyzed highly step‐ and atom‐economical benzofulvenation through free amine‐directed ortho C−H bond activation of o ‐arylanilines. This paper presents a novel, simple, and efficient approach for the synthesis of benzofulvene derivatives from o ‐arylaniline substrates through C−H bond activation with two diarylacetylenes as an implicit benzofulvene unit. The reactivity of synthesized benzofulvenes toward oxidation was investigated, and they were shown to transform into phenanthridines, oxabenzofulvenes, and fluorescent polycyclics. Abstract :